Analysis of Efficiency of Rotary Piston Engines Use at Power Plants for Surplus Electrical Energy Accumulation - Mytrofanov O.; Proskurin A (Problems of the Regional Energetics)
This article is devoted to the methods for enhancing the power plants’ efficiency in accumula-tion of a surplus electrical energy obtained using the renewable energy sources. The study is aimed at analyzing the efficiency of perspective power plants for accumulation of the surplus electricity in the form of compressed air based on rotary piston engines. To achieve the goal a comparative analysis of efficiency of diabatiс and adiabatic schemes of the electric energy stor-age was performed. The analysis was found to reveal the major advantages and disadvantages, along with the design features of each type of schemes. The main ways to increase the efficien-cy of the compressed air storage units, using the rotary piston engines as the electrical energy generators, were established. The experimental operational characteristics of the rotary piston engines showed that they are relevant to the parameters of the power units of air accumulation. The most significant results reveal that the methods for the analysis and of generalization have been used to develop the principal schemes of diabatic and adiabatic power plants for the accu-mulation of the surplus electrical energy in the form of compressed air using rotary piston en-gines, which require no additional air heating prior to expansion. The significance of the results obtained is that the use of the rotary piston engines being a part of the diabatic accumulation unit, allowed a complete exclusion of CO2 emission into the atmosphere.